The Effect of ESG Score on Stock Return: Do Financial Performance and Market Performance Moderate? - Dwi Nurnaningsih; Lilik Handajani (E-Jurnal Akuntansi, 2025)
The rising public attention on environmental and social issues, as well as corporate management strategies in addressing these issues, make ESG practices are crucial to observe. Therefore, this study is intended to examine the effect of ESG Score on Stock Return with Financial and Market Performance as moderating variables. The research method is associative quantitative, conducted on companies listed in ESG Sector Leaders IDX KEHATI Index from 2019 to 2023. There were 18 companies with the number of observations narrowed because there were a number of outlier data, resulting in 44 observations. Panel data were analyzed with Moderated Regression Analysis (MRA). The results of empirical testing show that ESG scores have a significant and positive effect on stock returns. And financial performance proxied through ROA strengthens the correlation of ESG scores and stock returns, while the ROE proxy is unable to moderate the relationship between the two variables. While, market performance (TQ) weakens the correlation between ESG scores and stock returns. In practical terms, this research contributes as a consideration for managers and investors to evaluate ESG adoption as an opportunity to attract sustainable investment. Keywords: ESG Score; Stock Return; Sustainability; Return on Assets; Tobin’s Q